Internet jako przestrzeń debaty na temat pluralizmu kulturowego: Percepcja internetowej mowy nienawiści skierowanej do uchodźców/imigrantów ekonomicznych (Politeja, 2019)
Internet as a Space for Debate on Cultural Pluralism. Perception of Online Hate Speech Targeted at Refugees/Economic MigrantsBeing an online space where members of the society can freely and instantaneously exchange their opinions, the Internet has become an ultra-attractive site for extended socio-political debate. At the same time, however, anonymity and global accessibility have transformed it into a tool facilitating the spread of hateful and radical messages, in particular those exploiting religious, ethnic and cultural differences. While multiculturalism and the “Other” have long been the subject of public debate, within this new mediatized public sphere problems and controversies surrounding them have thus acquired a new dimension. What can be observed is increasing social acceptance of verbal abuse and aggression in online communication, especially when it comes to attacks levelled at various “Others”. The article discusses the problem of multiculturalism and otherness in the Polish context, legal definitions used by the EU in their judgments on online hate speech, as well as the perception of hate speech targeted at refugees and immigrants among Polish people (aged 18-35). Some of the findings presented here are based on analyses conducted within the European project C.O.N.T.A.C.T., exploring various aspects of hate speech and hate crime in ten EU countries.